PENGARUH REDESTILASI CUKA KAYU GALAM (Melaleuca leucadendron Linn) TERHADAP PENGAWETAN IKAN - Setiawati, Evy (Kementerian Perindustrian, 2014)
To overcome the reduction of fish quality, almost all people preserve fish by formaldehyde. Therefore, it is necessary to find a substitute for food preservative that safe for health. One of the natural preservative is wood vinegar. The research aim was to investigate the effect of wood vinegar from wood Galam on fish preservation. Purification of wood vinegar used in this research was used redistilled based on boiling point. The making of Galam wood vinegar used temperature variation ≤100°C and 100 <x <200°C. The purification used temperature variation x≤1000C, 100<x≤1100C, and 110<x≤ 1200C. Fish preservation used redistilled vinegar by concentration of 2.5%, 5%, 7.5%, and 10%. Microbiological analysis included Total Plate Count and Fungus. Redistilled wood vinegar product were colorless clear, transparent, weak, pH from 2.52 to 2.73, specific gravity from 1.001 to 1.004, total acid from 16.75 to 42.34%. Fish preservation using 7.5% wood vinegar equal to 10%, but with different from 2.5% and 5%. Wood vinegar that had 7.5% concentration has the same effect to 10%, on the other hand, there is the greatest microbial growth treatment on 2.5% wood vinegar concentration. Based on the TPC, it can be said that the fish preservation could last up to 3 days at room temperature, and there was a significant microbial growth on the fifth day. Keywords: fish preservatives, redistilled, wood vinegar, galam wood